Extraction of lutein dye from Tagetes erecta garland waste for green dyeing of hemp fabric using response surface methodology - CHITICHOTPANYA, Pisutsaran; VUTHIGANOND, Nattaya; INPRASIT, Thitirat; KLAYKRUAYAT, Benjamas; SRISUK, Seranee (Journal of Metals, Materials and Minerals, 2022)
Large quantities of discarded flowers from religious observances are left at temples and other places of worship, causing global disposal and environmental issues. Recycling and transforming such organic waste into value-added products is one of the most effective and beneficial solutions to the problem. The main goal of this study is to convert the most abundant temple wastes of marigold (Tagetes erecta) flowers into an eco-friendly dyestuff for the textile industry. Our study assessed the suitability of dye extract from garland waste for dyeing hemp fabric and valuated indicators including color strength (K/S) and fastness properties using tannic acid as a bio-mordant. Response surface methodology (RSM) was used for optimization of the dyeing process and evaluation of the interaction effects of various operating parameters. The optimal conditions were determined to be pH of 4.23, dyeing temperature of 99.98°C, and dyeing time of 82.64 min. To validate the optimal conditions identified by RSM, performance evaluations were conducted, including color fastness properties of the dyed hemp fabrics as well as the total color difference after repeated standard washing. These results demonstrate the use of aqueous extract from temple garland waste combined with bio-mordant represents a promising approach for textile dyeing.